Not quite a doctor, but should I help? A qualitative exploration of medical students' attitudes towards responding to medical emergencies that occur in the public domain. Issue 4 (8th April 2019) - Xie, Jessica Ying-Yi; Frost, Rachael; Meakin, Richard
Abstract : Objective: To explore medical students' views on and experiences of responding to out-of-hospital medical emergencies. Setting: University College London (UCL). Participants: 11 UCL Medical School students. Study design: Qualitative. Methods and outcome measures: We carried out 11 one-to-one semistructured interviews, with participant validation and reflective work. The data were analysed using thematic analysis. Results: Three core themes were identified. (1) 'We Did Debate a Bit: Should We Go? Should We Not?'—Students' decisions to respond were based on the appearance of the casualty; the presence and actions of bystanders; witnessing the incident; self-perceived competence, confidence and knowledge; and personal experiences and feelings associated with medical emergencies. (2) 'It Would Represent the Medical Profession Well if We Did Step In and Help'—Students felt that they had an ethical and/or professional duty to help. (3) 'No One Should Die Because of a Lack of… Basic Life-Saving Techniques'—Students felt that medical school training alone had not sufficiently prepared them to respond to out-of-hospital medical emergencies. Improvements to training were suggested: integrating first aid/response training into the horizontal (systems-based) modules; teaching both common and less common medical emergencies and presentations; training that is led by experienced first responders and that increases students' exposure to out-of-hospital medical emergencies; and providing more revision training sessions. Conclusions: Students felt that medical school training could be improved to better prepare them for responding to out-of-hospital medical emergencies, and wanted clarification on whether or not they have an ethical and/or professional duty to help. Further mixed-methods research using a larger sample needs to be carried out to confirm whether findings are transferable to other UK medical schools.